Strategies of it puts understanding reader and styles of learning in university students - Wong, Fanny (2011)
The research presented aims to establish the relationship from reader ́s metacomprehension strategies with learning styles in college students. Participants were 809 students from both sexes who were applied the Strategies Inventory Schmitt metacomprehension of Inventory and Kolb’s Learning Strategies. The results showed that participants have a low level of development strategies and no evidence a metacomprehension predominant learning style. Finally, no relationship was found between metacomprehension reading strategies and learning styles.